PENERAPAN HAD POTONG TANGAN PADA KASUS PENCURIAN (Analisis Surat Al-Maidah Ayat 38 Berbasis Hadis) - Putri, Reiza Tri Anggraini; Rahmi, Shaffira (LP2M Universitas PTIQ Jakarta, 2023)
Theft is a crime that often occurs in society with various targets. The rampant theft that has occurred has caused unrest for the local community. Because, theft is not more or less done by the way the perpetrator of theft kills the victim so that his crime is not known to anyone. For this reason, handling is needed in overcoming this crime of theft by applying Islamic law so that the perpetrators are deterred and the community lives peacefully. The main issues that we will examine in this study are: Analyzing the punishment of cutting hands in theft contained in Qs. Al-Maidah: 38 where the perpetrators of theft, both men and women who commit theft, will be subject to Had Amputation. relates to Hand Amputation and will provide conclusions regarding the application of Hand Amputation in Theft